Peran Media Sosial dalam Peningkatan Kesadaran Merek dan Penjualan - Fiki Fiki; Fadhur Rosy; Mashudi Mashudi (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
Social Media has become an effective communication tool in building and increasing brand awareness and sales to carry out marketing or promotional activities of a product online or social media. This article aims to determine the role of social media in increasing brand awareness and sales. The method used in this study is to use the kualitatif method. The results of this study are the utilization of the role of social media in increasing brand awareness and sales as a promotional tool provides minimal cost benefits and the ability to reach many people. Social media also helps in the dissemination of information and can interact directly with consumers so that it becomes the right medium in increasing brand awareness and sales.